Synthesis, structure, and photophysics of copper(i) triphenylphosphine complexes with functionalized 3-(2′-pyrimidinyl)-1, 2, 4-triazole ligands. Issue 38 (25th September 2017) - Chen, Jing-Lin; Zeng, Xue-Hua; Luo, Yan-Sheng; Wang, Wan-Man; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui; Huang, Shuping; Liu, Li; Wong, Wai-Yeung
Abstract : The use of CF3 group can enhance the solid-state luminescence of 1, 2, 4-triazole-based Cu(i ) complexes but the use of Bu t and pyrimidinyl groups and the 1, 2, 4-triazolyl-NH deprotonation do not favor this. Abstract : A series of new mononuclear and dinuclear copper(i ) triphenylphosphine complexes with functionalized 3-(2′-pyrimidinyl)-1, 2, 4-triazole ligands have been synthesized and characterized, in which functionalized 3-(2′-pyrimidinyl)-1, 2, 4-triazole adopts neutral mono- and bis-chelating coordination modes and a mono-anionic bis-chelating binding manner due to the 1, 2, 4-triazolyl-NH deprotonation. All these Cu(i ) complexes display a relatively weak low-energy absorption in a CH2 Cl2 solution, ascribed to the charge-transfer transitions with appreciable MLCT character, as suggested by TD-DFT analyses. These Cu(i ) complexes are all emissive in solution and in the solid state at ambient temperature, and their luminescence properties can be well modulated via the addition of the second {Cu(PPh3 )2 } unit and modification of 3-(2′-pyrimidinyl)-1, 2, 4-triazole involving the N–H deprotonation and the substituent variation of the 1, 2, 4-triazolyl ring. It is also demonstrated that introducing the trifluoromethyl group into the 1, 2, 4-triazolyl ring is helpful for enhancing the solid-state luminescence properties of the 1, 2, 4-triazole-based Cu(i ) complexes, whereas the introduction of the tert -butyl group into the 1, 2, 4-triazolyl ring, the 1, 2, 4-triazolyl-NH deprotonation, and the use of the pyrimidinyl ring instead of the pyridyl ring are all unfavorable.